Engineering of high-density thin-layer graphite foam-based composite architectures with superior compressibility and excellent electromagnetic interference shielding performance - Li, Hongling (2020)
Three-dimensional (3D) graphene architectures with well-controlled structure and excellent physiochemical properties have attracted considerable interest due to their potential applications in flexible electronic devices. However, the majority of the existing 3D graphene still encounters several drawbacks such as brittleness, non-uniform building units, and limited scale (millimeter or even micrometer), which severely limits its practical applications. Herein, we demonstrate a new scalable technique for the preparation of thin-layer graphite foam (GF) with controllable densities (27.2-69.2 mg cm-3) by carbonization of polyacrylonitrile using a template-directed thermal annealing approach. By integrating the GF with poly(dimethylsiloxane) (PDMS), macroscopic porous GF@PDMS with variable thin-layer GF contents ranging from 15.9 to 31.7% was further fabricated. Owing to the robust interconnected porous network of the GF and the synergistic effect between GF and PDMS, GF@PDMS with a 15.9% thin-layer GF content exhibited an impressive 254% increase in compressive strength over the bare GF. In addition, such 15.9% GF@PDMS can totally recover after the first compression cycle at a 95% strain and maintain ∼88% recovery even after 1000 compression cycles at an 80% strain, demonstrating its superior compressibility. Moreover, all of the as-prepared GF@PDMS samples possessed high electrical conductivity (up to 34.3 S m-1), relatively low thermal conductivity (0.062-0.076 W m-1 K-1), and excellent electromagnetic interference shielding effectiveness (up to 36.1 dB) over a broad frequency range of 8.2-18 GHz, indicating their great potential as promising candidates for high-performance electromagnetic wave absorption in flexible electronic devices.